LITERATURE REVIEW: CORELATION OF PHYSICAL AND STRESS CONDITIONS TO ANXIETY LEVELS OF PREGNANT WOMEN DURING A PANDEMIC - Rizda Nabila, Anisa; Kurniasari, Lia (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
This study was used A simple comprehensive Literature Review methodology. The articles for the literature review were chosen from both domestic and foreign periodicals. Google Scholar, Elsevier, PubMed, and Willey Library databases were used to search for the publications. Overall, it can be inferred from those publications that there is a correlation between stress conditions and pregnant women's anxiety levels during the pandemic, as well as between physical activity and anxiety levels. Pregnant women who exercise dramatically lessen their anxiety, especially during the epidemic period. Pregnant women experience stress for a variety of reasons, including their way of life, their families, and their economic situation, as well as their anxiety over access to prenatal care. The advantage of this.